Optimization Strategy Of Regional Origin Income (PAD) And Impact On Economic Growth In Buton Selatan Regency - Musa, La; Abdul Rahman Kadir; Nur Dwiana Sari Saudi (Economy and Finance Enthusiastic, 2023)
South Buton Regency has various potential natural resources, such as fertile agricultural land, abundant fishery products, and large reserves of minerals and mines. However, this potential has yet to be fully optimized to increase local revenue (PAD). This study aims to identify strategic factors, which are strengths and weaknesses as well as opportunities and threats, and then formulate priority development strategies for optimizing Regional Original Revenue (PAD) and their impact on economic growth in South Buton Regency. Primary data is used through field observations and interviews, while secondary data is obtained from previous research, books, and related agencies. The results of the study indicate alternative strategies that can be considered, including strategies for exploiting the potential of rich natural resources and improving supporting infrastructure, strategies for implementing training and education programs and increasing efforts to diversify the economy, strategies for using the potential for rich natural resources to develop various products and services as well as improving the quality of existing infrastructure and forging partnerships with other regions in a joint effort to overcome competition with other regions and face common challenges.